2019
DOI: 10.1007/978-981-15-0602-4_27
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and the Immune Response

Abstract: Innate immunity and adaptive immunity play critical roles in maintaining normal physiological functions and the development of diseases. In innate immune responses, heterogeneous autophagy can directly remove intracellular pathogens while activating PRRs, including TLRs and NLRs, to trigger their signal transduction pathways and promote NKT cell activation, cytokine secretion, and phagocytosis. In adaptive immune responses, the autophagy reaction has an important effect on the homeostasis, function, and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 19 publications
0
69
0
Order By: Relevance
“…Inasmuch as autophagy is a process of the removal of damaged organelles and misfolded or aggregated proteins, it plays a critical role in preventing inflammatory diseases [ 49 ]. Specifically, it has been demonstrated that naive T cells exiting from the thymus depend on autophagy-related mitochondrial content reduction [ 50 ]. Furthermore, the loss of ATG5 in T cells was shown to result in an inflammatory response and a loss of tolerance [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inasmuch as autophagy is a process of the removal of damaged organelles and misfolded or aggregated proteins, it plays a critical role in preventing inflammatory diseases [ 49 ]. Specifically, it has been demonstrated that naive T cells exiting from the thymus depend on autophagy-related mitochondrial content reduction [ 50 ]. Furthermore, the loss of ATG5 in T cells was shown to result in an inflammatory response and a loss of tolerance [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been demonstrated that naive T cells exiting from the thymus depend on autophagy-related mitochondrial content reduction [ 50 ]. Furthermore, the loss of ATG5 in T cells was shown to result in an inflammatory response and a loss of tolerance [ 50 ]. Indeed, the reduction in the expression of Atg genes observed in the SEB+Veh group may be a factor in the induction of inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In the innate immune response, autophagy not only contributes to the clearance of pathogens, but also participates in protection against toxins, and impacts cytokine production. In terms of the adaptive immunity, autophagy plays crucial roles in T cell maturation and differentiation, as well as antigen presentation [23]. However, the relationship between AhR and autophagy in the skin has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, natural secretion of IL-17 and IL-22 by γδ T cells can be regulated by IL-1-dependent autophagy activation (123). Moreover, in antigen donor cells, upon severe stress exposure (which might be prolonged in time), cell death will take place, causing autophagy-mediated antigen release and stimulation of immune and inflammatory responses (124).…”
Section: Autophagy and The Immune Systemmentioning
confidence: 99%
“…Several studies indicate that a piece of active autophagic machinery produces tumor-specific antigens in tumor cells which, after their release due to antigen donor cells, boost antitumor effects by enhancing antigen presentation and subsequent T cell activation (120). Autophagy induces liberation of more ATPs as a required signal to stimulate recruitment of antigen-presenting cells (APCs) and tumor sensitivity to cytotoxic T lymphocytes (124). Also, inhibition of autophagy by targeted drugs or genetic deficiencies in autophagyrelated genes such as ATG5, ATG7, ATG12, Beclin-1, and VPS34 reduces ATP release and hinders the recruitment of required immune cells from boosting antitumor immune responses (125).…”
Section: Autophagy and The Immune Systemmentioning
confidence: 99%